CT STAGING THAT UNVEILS A MYSTERY – ASYMPTOMATIC PHEOCHROMOCYTOMA ASSOCIATED WITH NEUROFIBROMATOSIS TYPE 1 - Mokhtar, Muzhaffa; MA, Masliza Hanuni; WA, Siti Sanaa; Mohamad, Hussain; Muda, Nor Hisham (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Pheochromocytomas and paraganglioma (PPGL) are catecholamine-secreting tumours, derived from chromaffin cells. The classical triad comprises paroxysms of headache, palpitation, and diaphoresis. About 10% of patients are asymptomatic. At least one-third of patients with PPGLs have hereditary disease caused by germline mutations. This includes neurofibromatosis type 1 (NF-1) which may predispose patients to pheochromocytoma and occurs in 0.1-5.7% of cases. We report a case of a 57-year-old female with hypertension and diabetes who was referred from the surgical team after an incidental finding of a right adrenal mass on abdominal CT performed for rectal adenocarcinoma staging. She denied paroxysms or other symptoms that suggest catecholamine or cortisol excess. Blood pressure was well controlled with a single agent. Examination revealed axillary freckling, multiple cafè au lait spots and generalized cutaneous nodules which were present since adolescence. CASE Serial abdominal CT scans showed increasing size of right adrenal mass measuring 4.4 x 5.4 x 5.9 cm (previously 4.4 x 5.1 x 5.6 cm) with presence of fluid-fluid level within, with HU ranging from HU 20 (anteriorly) and HU 70 (posteriorly). Metanephrine 5.42 umol/L (0.33- 1.53), normetanephrine 8.0 umol/L (0.88-2.88) and 3-methoxytyramine 1.16 umol/L (0.66-2.60) were elevated on 24-hour urine collection. Thyroid function test and serum calcium were normal. Histopathological examination of the cutaneous nodule confirmed neurofibromas. She underwent open right adrenalectomy and HPE was consistent with pheochromocytoma. Three months post adrenalectomy, urine metanephrines had normalized, and there was no tumor residual or recurrence on CT imaging. She no longer requires any anti-hypertensive drug, and we were able to withdraw insulin therapy. CONCLUSION Though rare, the combination of NF-1 with pheochromocytoma in our patient is an offbeat presentation of adrenal incidentaloma in a patient with multiple cutaneous nodules, hypertension and diabetes. Screening for pheochromocytoma should be done in a patient with NF-1 and hypertension. Prompt treatment will alleviate the detrimental effect of catecholamine excess and improve the patient’s quality of life.